PENDIDIKAN DAN INDEPENDENSI PEREMPUAN MASA KINI - Hermanto Hermanto (AN-NISA, 2018)
Education is a right for every person in the world. Therefore, there is no excuse to discriminate the education for women in Indonesia. This article is targeted to discuss the importance of education and independence of women, especially the independence of the family economy area. Woman who has a wider knowledge and more competent economic skill will be more independent, strong, and will be more successful to run her role and her function in the family, society, and national development.